Cyclodextrin-Calcium Carbonate Micro- to Nano-Particles: Targeting Vaterite Form and Hydrophobic Drug Loading/Release - Cléa Chesneau; Alpha Oumar Sow; Fadila Hamachi; Laurent Michely; Séna Hamadi; Rémy Pires; André Pawlak; Sabrina Belbekhouche (MDPI AG, 2023)
Tailor-made and designed micro- and nanocarriers can bring significant benefits over their traditional macroscopic counterparts in drug delivery applications. For the successful loading and subsequent release of bioactive compounds, carriers should present a high loading capacity, trigger release mechanisms, biodegradability and biocompatibility. Hydrophobic drug molecules can accumulate in fat tissues, resulting in drawbacks for the patient's recovery. To address these issues, we propose to combine the advantageous features of both host molecules (cyclodextrin) and calcium carbonate (CaCO3) particles in order to load hydrophobic chemicals. Herein, hybrid cyclodextrin-CaCO3 micro- to nano-particles have been fabricated by combining Na2CO3 solution and CaCl2 solution in the presence of an additive, namely poly (vinylsulfonic acid) (PVSA) or glycerol (gly). By investigating experimental parameters and keeping the Na2CO3 and CaCl2 concentrations constant (0.33 M), we have evidenced that the PVSA or gly concentration and mixing time have a direct impact on the final cyclodextrine-CaCO3 particle size. Indeed, by increasing the concentration of PVSA (5 mM to 30 mM) or gly (0.7 mM to 4 mM) or the reaction time (from 10 min to 4 h), particles with a size of 200 nm could be reached. Interestingly, the vaterite or calcite form could also be selected, according to the experimental conditions. We hypothesised that the incorporation of PVSA or gly into the precipitation reaction might reduce the nucleation rate by sequestering Ca2+. The obtained particles have been found to keep their crystal structure and surface charge after storage in aqueous media for at least 6 months. In the context of improving the therapeutic benefit of hydrophobic drugs, the developed particles were used to load the hydrophobic drug tocopherol acetate. The resulting particles are biocompatible and highly stable in a physiological environment (pH 7.4, 0.15 M NaCl). A selective release of the cargo is observed in acidic media (pH lower than 5).